Caracterização da produção em toros do cogumelo comestível Lentinula edodes (Berk.) Pegler na região oeste do Estado de São Paulo - de Queiroz Neves, Cilene Ferreira [UNESP]; Graciolli, Luiz Antonio [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
This study was carried out in the towns of Dracena, Junquciropolis, Mirandopolis, Aliancas, Ilha Solteira, Castilho, Aracatuba, Birigui and Guararapes, São Paulo State, by surveying 17 Shiitake growers through a questionnaire. Data pertaining to the stages of log-Shiitake growing, recording and characterization of growers and growing systems were entered into Microsoft Excel for Windows. The results showed that Shiitake cultivation is recent and increasing in this region, and that growers have a high education level. Shiitake cultivation is mainly located in rural areas, with both Brazilians of Japanese descent and native Brazilians growing it. The most commonly used trees are eucalyptus and mango. The high level of log contamination is perhaps due to growing without temperature or moisture control and to the inappropriate growing system.. In 2004, there were 45,000 Shiitake-inoculated logs in this region, and the yield stood around 200 g of fresh mushroom/log. The mushrooms are picked in boxes of 200 g, and are sold mainly to Ceasa in open markets.
Characterization of log cultivation of the edible mushroom Lentinula edodes (Berk.) Pegler in western São Paulo State (Brazil)
Keywords: Shiitake; edible fungi; growing system; production